ABUNDANCE AND UTILIZATION OF NATURAL LIFE FEED FOR REARING OF ASIAN CATFISH (Pangasianodon hypophthalmus) LARVAE IN OUTDOOR POND - Didik Ariyanto; Evi Tahapari (Indonesian Aquaculture Journal, 2016)
In early rearing period, the larvae of Asian catfish (Pangasianodon hypophthalmus) were fed with Artemia nauplii at the first 10 days. Since Artemia cyst price is quite expensive, it will be a constraint in development of the Asian catfish hatcheries. This study was conducted to evaluate the abundance of natural life food in pond and utilization of it for substitute Artemia cyst in Asian catfish larvae rearing. The Asian catfish larvae at the age of 5 days after hatching were used as the test fish. Sampling of natural life food in fertilized pond was conducted before the fish stocked. The fish larvae were stocked in pond after ten days from ponds fertilizing. At the 2nd day after larvae fish was stocked, five fish samples were collected for identify the type of food which consumed by fish. The results showed that abundance of natural life food which found in ponds ranged from 70,200 to 180,600 individual/L. Index of diversity, uniformity and dominancy for phytoplankton and zooplankton ranged from 2.407 to 2.732; from 0.032 to 0.043 and from 0.112 to 0.204, respectively. Based on the analysis of digestive tract of fish, it was found that index of selectivity and index of preponderance for natural life food ranged from 0.94 to 0.62 and from 0.17 to 67.03, respectively. This study suggested that Asian catfish larvae at the age of five days after hatching can utilize the natural life food in ponds to replace the use of Artemia cyst in indoor hatchery system.